Assessment of various soybean varieties [Glycine max (L.) Merrill.] on the stability of manifestation of economically valuable traits - О. З. Щербина; С. О. Ткачик; О. О. Тимошенко; Н. О. Шостак (Plant Varieties Studying and Protection)
Purpose. To study the protein content and other economically valuable traits in soybean varieties of various origin, to determine the stability and plasticity indicators of these traits, as well as to identify varieties that are promising for use in breeding programs. Methods. Field, laboratory, biochemical and statistical. Results. In total 22 soybean varieties of various origin in terms of yield, protein and oil content in seeds were investigated. High-yield and high-plasticity varieties are distinguished: ‘Muza’, ‘Mentor’, ‘Asuka’, ‘Valas’, ‘Kofu’, ‘Asuka’, ‘Cardif’, ‘Alligator’, ‘Vyshyvanka’, ‘Suziria’ and varieties of domestic breeding with stable yield ‘Siverka’, ‘Vilshanka’, ‘Ustia’, and also the ‘Lisbon’ variety. High protein content was noted in the variety ‘Opus’ – 45.0% in 2017. This variety on average for three years showed 43.63% of the protein in the seeds, and was second after the ‘Ustia’ variety (44.3%). The highest value of the regression coefficient b = 4.289 was observed in the ‘Lisbon’ variety, which shows its high sensitivity to growing conditions with a fairly low average seed protein content of 38.60%, as well as the variety ‘Silesia’ b = 4.289 with an average protein value of 42,73%. Standard variety ‘Muza’ with a low protein content of 38.60% was quite stable in the expression of this characteristic – S2 = 0.222. A number of high-oil varieties were distinguished: ‘Valas’ – 22.77%, ‘Sigalia’ – 22.7%, ‘Alligator’, ‘Siverka’ – 22.53%, ‘Kofu’ – 22.13%, standard variety ‘Muza’ – 21.77%. Conclusions. In breeding programs aimed at increasing the protein content in seeds, the following varieties should be used: ‘Opus’ – as a carrier of the maximum value of the trait, as well as ‘Ustia’, ‘Asuka’, ‘Silesia’ and ‘Kasidi’ as combining high yield and high protein content. The weather conditions of the year in different ways influenced on the manifestation of the studied traits: in a favorable year for obtaining high yields, the protein content in the seeds decreased, the high protein content accumulated in a drier year, and the oil content in seeds changed insignificantly.